Postnatal Role of the Cytoskeleton in Adult Epileptogenesis. Issue 1 (17th June 2020) - Gavrilovici, Cezar; Jiang, Yulan; Kiroski, Ivana; Teskey, G Campbell; Rho, Jong M; Nguyen, Minh Dang
Abstract: Mutations in cytoskeletal proteins can cause early infantile and childhood epilepsies by misplacing newly born neurons and altering neuronal connectivity. In the adult epileptic brain, cytoskeletal disruption is often viewed as being secondary to aberrant neuronal activity and/or death, and hence simply represents an epiphenomenon. Here, we review the emerging evidence collected in animal models and human studies implicating the cytoskeleton as a potential causative factor in adult epileptogenesis. Based on the emerging evidence, we propose that cytoskeletal disruption may be an important pathogenic mechanism in the mature epileptic brain.